THE EFFECTIVENESS OF TEACHER FEEDBACK TECHNIQUE TOWARD STUDENTS WRITING ABILITY (AN EXPERIMENTAL STUDY AT SMA MUHAMMADIYAH 2 METRO) - Andianto, Andianto (Jurnal Pedagogy, 2016)
The objective of this research are to examine whether: 1) there is a different between teacher feedback technique and conventional technique toward students’ writing ability at the first grade students of SMA Muhammadiyah 2 Metro and 2) the effectiveness of Teacher Feedback Technique toward students’ writing ability. This method applied in this research was a quasi experimental research. It was conducted at the first grade students of SMA Muhammadiyah 2 Metro. It consists of 90 students in three Classes. The sample of the research were two classes. Sampel penelitian ini adalah kelas X1 dan X2 yang dipilih menggunakan teknik cluster random sampling. The data were analyzed by using T-Test with Minitab Version 16 and Normalized Gain Test. Based on the result of data analysis, there are some research findings that can be drawn. They are; 1) there is a different between students’ writing ability tough by using teacher feedback and conventional technique to the students of SMA Muhammadiyah Metro. Teacher feedback technique is more effective than conventional technique toward students writing ability. 2) the level of effectiveness of Teacher Feedback Technique is 0.32 (medium) and Conventional technique is 0.17 (low).